Sara Baartman and the objectification of black woman (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This article seeks to analyze the contemporary representation of the black woman's body through its connection with the story of Sara Baartman, the African woman who was exposed to Europeans as entertainment at the beginning of the 19th century. Thinking about the black woman's body implies thinking about the place this woman occupies in today's society. To this end, we will look at the correlation between the slave vision of the black woman's body as something available to the white man, the image of the black female body in the cultural production of mass consumption in the 20th and 21st centuries, and its maintenance at the bottom of the socio-occupational pyramid in Brazil. The denial of a voice to these women appears to be the final factor in the attempt to relegate them to a permanent social status of inferiority, which can only be changed through their growing political activism, inserting their agendas into national and international debates.
Keywords: Sara Baartman; black woman; objectification; political activism